BLOOD GROUP AFFILIATION OF THE CONTEMPORARY BULGARIAN POPULATION FROM THE AREA OF SHUMEN: BLOOD GROUP AFFILIATION OF THE CONTEMPORARY BULGARIAN POPULATION FROM THE AREA OF SHUMEN - Todorov, Velislav; Boycheva, Maria; Boichev, Milen (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The present research studied the blood group affiliation to the AB0 and Rhesus factor systems of 200 people (100 men and 100 women) from the region of Shumen in comparison with a control group of contemporary Bulgarian population. The comparison revealed that in the group from the Shumen region there was an increase in the prevalence of groups 0 and B, and a decrease in the frequency of Rh-. Such a configuration is also observed in the comparison of Europeans with persons of Mongoloid origin. The obtained results give grounds to establishing a presence of certain eastern (Mongoloid) characteristics in the ethnogenesis of the population to which the studied individuals belong.